The Return of the Stock Market on the Pandemic Situation of Covid 19 in Thailand within the Next Decade - Teanboonsong, Twatchai (Journal of Thammawat, 2022)
The article of "The return of the stock market on the pandemic situation of Covid 19 In Thailand within the next decade" has an objective to study the impact of the Covid-19 pandemic and the return of the stock market. From the study, it is found that Thailand and Thai people are affected both economically and socially. The impact was severe after the government lock-down to prevent people from traveling, resulting in disruption of the economic circulation system. Entrepreneurs lack cash flow, inevitably need to reduce employment or temporarily close the business. The government has to pay money to remedy the people who have suffered. The overall result would affect the gross domestic product which tends to decrease. Although, some businesses can be operated, trading is difficult. The study also found that the governments must stabilize the political system. They have to develop and create the set of proper economic and social policies for national administration. They have to build credibility in order to give investors more confidence and courage to invest. They have to develop education systems for the new generation to be in line with current environment, create the ability to earn a living or create a system of analytical thinking that can be transformed into new technology to be used for further economic benefits. Governments and the private sector must jointly support sustainable agriculture as well as increasing the value of agricultural products. The government should use the geographic advantages that Thailand has, whether it is to develop the rail system to become a transportation hub of ASEAN, or to create incentives for foreign companies to invest more in Thailand in order to transfer technology and innovation to us.